2015
DOI: 10.1021/ic502551n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Physical Properties of the New Transition Metal Oxyselenide Ce2O2ZnSe2

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…For example, Kerman et al have demonstrated that a simulated annealing approach to determining which modes are important can be used to deduce the true P2 1 /n symmetry of room temperature WO 3 . Evans and co‐workers have shown that this approach can also be used to determine the pattern of metal occupancies in a complex family of oxychalcogenides.…”
Section: Structure Solution Proceduresmentioning
confidence: 99%
“…For example, Kerman et al have demonstrated that a simulated annealing approach to determining which modes are important can be used to deduce the true P2 1 /n symmetry of room temperature WO 3 . Evans and co‐workers have shown that this approach can also be used to determine the pattern of metal occupancies in a complex family of oxychalcogenides.…”
Section: Structure Solution Proceduresmentioning
confidence: 99%
“…One important family of compounds is those with general composition Ln 2 O 2 MSe 2 (Ln = La, Ce; M = Mn, Fe, Zn, Cd) [3][4][5][6][7][8][9][10][11] and closely related composition such as La 2 O 2 Cu 2−4x Cd 2x Se 2 [12]. These materials are semiconductors with band gaps varying from ∼0.3 to ∼3.3 eV [1,[3][4][5]8,10,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant recent research on oxychalcogenide materials due to their important electronic and magnetic properties and the area has been recently reviewed [1][2]. One important family of compounds is those with general composition Ln2O2MSe2 (Ln = La, Ce; M = Mn, Fe, Zn, Cd) [3][4][5][6][7][8][9][10][11] and closely related composition such as La2O2Cu2-4xCd2xSe2 [12]. These materials are semiconductors with band gap varying from ~0.3 eV to ~ 3.3 eV [1, 3-5, 8, 10-11, 13-16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous new compounds with the general formula RE 2 TSe 2 O 2 (RE = La, Ce; T = Cd, Fe, Mn, Zn) [1][2][3][4][5][6][7][8][9] have been discovered and their structures and magnetism have been studied. Among the particular families, different polymorphs may exist which makes the diversity even bigger.…”
Section: Introductionmentioning
confidence: 99%